Helping Your Child with Social Problems - Millie Ferrer; Anne M. Fugate (EDIS)
When your child comes to you with a social problem, you can help him using the process in this document. By using this process, you give your child support and encouragement and also show him a way to solve problems. This document is FCS2027, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. Published: May 2003.